Analysis of Backyard Poultry Production in Ondo State, Nigeria - Amos, T.T. (International Journal of Poultry Science, 2006)
The study examined the profitability of Poultry production in Ondo State. A total of 92 Poultry farmers were selected from two LGAs in the State and used for the study. The study revealed that backyard poultry production (Layers and Broilers) is a profitable venture in the study area. Layers production was observed to be more profitable than broilers production. Factors affecting the production of layers in the area include cost of feeding and veterinary cost while for broilers they include cost of feed and production experience. The study concluded with suggestions for increasing the productivity of poultry production in the study area in particular and Nigeria in general.